Crack propagation methodology under complex loadings. (July 2015) - Dompierre, Benoît; Mesbah, Majid; Wyart, Eric
Highlights: An advanced methodology for crack propagation analysis is demonstrated. CCF interaction, eigenmode actualization and load spectrum management are all included in the methodology. The methodology is validated by comparison between numerical and experimental results. Abstract: In this paper, a novel methodology for analyzing crack propagation under complex loadings is presented. It includes various kinds of complexities such as multiple non-proportional load cases, LCF/HCF interaction, eigenmode actualization and load spectrum under proportional loading. After being validated on simple test cases, this methodology is applied on two full-scale industrial cases. The results demonstrate that this methodology, when compared to simulations using simplified load cases, has a great impact on fatigue life assessment. This methodology achieves higher accuracy and more representative results and therefore can lead to more radical optimization in a design process.